State and social revolutions: a comparative analysis of France, Russia, and China - Skocpol, Theda (London, 1979)
Some books present fresh evidence; others make arguments. that urge the reader to see old problems in a new light. This work is decidedly of the latter sort. It offers a frame of reference for analyzing social-revolutionary transformations in modern world history. And it uses comparative history to work out an explanation of the causes and out comes of the French Revolution of 1787-1800, the Russian Revolution of 1917-1921, and the Chinese Revolution of 1911-1949. Developed through critical reflection on assumptions and types of explanation com mon to most received theories of revolution, the principles of analysis sketched in the first chapter of the book are meant to reorient our sense of what is characteristic of-and problematic about-revolutions as they ac tually have occurred historically. Then the remainder of the book attempts to make the program of Chapter 1, calling for new kinds of explanatory arguments, come alive in application. In Part I, the roots of revolutionary crises and conflicts in France, Russia, and China are traced through anal yses of the state and class structures and the international situations of the Bourbon, Tsarist, and Imperial Old Regimes. Particular emphasis is placed upon the ways in which the old-regime states came into crisis, and upon the emergence of peasant insurrections during the revolutionary interreg nums. Then, in Part II, the Revolutions themselves are traced from the original outbreaks through to the consolidation of relatively stable and distinctively structured New Regimes: the Napoleonic in France, the Sta linist in Russia, and the characteristically Sino-Communist (after the mid 1950s) in China. Here special attention is paid to the state-building efforts of revolutionary leaderships, and to the structures and activities of new state organizations within the revolutionized societies. In their broad. sweep from Old to New Regimes, the French, Russian, and Chinese Revo lutions are treated as three comparable instances of a single, coherent social-revolutionary pattern. As a result, both the similarities and the individual features of these Revolutions are highlighted and explained in ways somewhat different from previous theoretical or historical discussions.
Keywords: Sociology